THE EFFECT OF INFORMATION TECHNOLOGY CAPABILITIES IN IMPLEMENTING, INFORMATION SECURITY MANAGEMENT SYSTEMS - Ali alkasasbeh, Anas (European Scientific Journal, ESJ, 2014)
This study aimed to measure The Effect of Information Technology Capabilities in Implementing Information Security Management Systems; Study of Commercial banks in Jordanian capital, Amman. The study sample included 14 Commercial banks in Amman Jordanian capital city that adopted IT. The study results show that there is direct relationship between effect of Information Technology Capabilities and Implementation of Security Information Management Systems in Jordanian banks. Based on the results of the study, the research proposed several recommendations to commercial banks, most importantly on how to take care of its IT capabilities In order to Increase their operations in Implementing Information Security Management Systems.